2017
DOI: 10.24193/adn.10.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Mathematics Teachers’ Views about GeoGebra and Its Use

Abstract: Abstract:The purpose of this study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This research have shown that teachers' beliefs were transformed to some extent in favour of the use of GeoGebra, as well as using constructivist ideas in their mathematics teaching can be attained through PD. This study, similar to other studies (Baltaci, Yildiz & Kosa, 2015;Horzum & Unlu, 2017;Kaleli Yilmaz, 2015;Mainali & Key, 2012;Tatar, 2013;Zakaria & Lee, 2012), showed that participants developed positive beliefs towards GeoGebra after a PD program based on GeoGebra for teachers. This experience arise due to novelty of GeoGebra that helped to activate participants' interest-excitement.…”
Section: Discussionsupporting
confidence: 91%
“…This research have shown that teachers' beliefs were transformed to some extent in favour of the use of GeoGebra, as well as using constructivist ideas in their mathematics teaching can be attained through PD. This study, similar to other studies (Baltaci, Yildiz & Kosa, 2015;Horzum & Unlu, 2017;Kaleli Yilmaz, 2015;Mainali & Key, 2012;Tatar, 2013;Zakaria & Lee, 2012), showed that participants developed positive beliefs towards GeoGebra after a PD program based on GeoGebra for teachers. This experience arise due to novelty of GeoGebra that helped to activate participants' interest-excitement.…”
Section: Discussionsupporting
confidence: 91%
“…In mathematics education, GeoGebra is one of the popular dynamic software that is beneficial to individuals' professional development [23]. GeoGebra was simpler to use by pre-service instructors than other dynamic mathematics software [24].…”
Section: Introductionmentioning
confidence: 99%
“…In line with opinion Suarsana et al, (2019) Interactive learning media will provide a real and effective learning experience during learning activities Another thing that is also very important in learning mathematics is the use of technology according to Yates et al (2021), the use of technology is needed so that the student learning experience becomes more effective, in this digital LKPD, it is equipped with illustrations developed through interactive geogebra in every activity with the aim of making learning activities more effective and having a good positive impact on learning. In line with opinion Horzum et al, (2017) that geogebra has many positive impacts, starting from improving students' abilities, developing positive attitudes of students in learning, increasing students' understanding, thinking and visualization. In addition, due to the situation of students who are increasingly disinterested in learning mathematics during online learning (Hima et al, 2021), the use of this digital LKPD fosters student interest in learning activities, because of its new and interactive features, fostering positive student attitudes in learning (Horzum et al, 2017) such as having a desire to explore and participate in learning.…”
Section: Trial Processmentioning
confidence: 58%
“…In line with opinion Horzum et al, (2017) that geogebra has many positive impacts, starting from improving students' abilities, developing positive attitudes of students in learning, increasing students' understanding, thinking and visualization. In addition, due to the situation of students who are increasingly disinterested in learning mathematics during online learning (Hima et al, 2021), the use of this digital LKPD fosters student interest in learning activities, because of its new and interactive features, fostering positive student attitudes in learning (Horzum et al, 2017) such as having a desire to explore and participate in learning. This is in accordance with one of the functions of learning media which is also used to foster student interest in learning (Astuti et al, 2019).…”
Section: Trial Processmentioning
confidence: 58%